Senam Yoga Terhadap Tingkat Kecemasan Ibu Hamil Trimester III - Nur Alfi Fauziah; Komalasari Komalasari; Inggit Primadevi; Atik Farokah (Universitas Aisyah Pringsewu, 2021)
Anxiety is discomfort or fear accompanied by a response that occurs in the third trimester, namely anxiety about perineal tears (64%), pain during labor (60%), loss of babies (50%), and fetal abnormalities (50%). One of the treatments done to reduce anxiety in pregnant women is physical exercise, such as meditation / yoga. The aim was to determine the effect of yoga exercises on the anxiety level of third trimester pregnant women at BPM Sri Nowo Retno Punggur Central Lampung in 2020. This type of research is quantitative with a pre-experimental design using a one group pretets postest approach. The population was all third trimester pregnant women at BPM Sri Nowo Retno as many as 35 pregnant women, the sample used was 35 pregnant women with a purposive sampling technique. The data analysis used was using paired t test. The results of the analysis showed that the average anxiety before being given exercise was 26.00, after being given exercise was 22.40, the difference in the average value of anxiety before and after being given yoga exercise was 3,600, then the p-value was 0,000 which means that there is an effect of yoga exercises on the level anxiety of third trimester pregnant women. It is hoped that the results of this study can be used as a source of information to increase the knowledge of pregnant women, so that pregnant women can apply yoga exercises as a method to reduce anxiety.Kecemasan adalah ketidaknyamanan atau rasa takut yang disertai suatu respons yang terjadi pada trimester III yakni cemas terhadap robekan perineum (64%), nyeri selama persalinan (60%), kehilangan bayi (50%), dan kelainan janin (50%). Salah satu asuhan yang dilakukan untuk mengurangi kecemasan pada ibu hamil adalah latihan fisik, seperti meditasi/yoga. Tujuannya adalah untuk mengetahui pengaruh senam yoga terhadap tingkat kecemasan ibu hamil trimester III di BPM Sri Nowo Retno Punggur Lampung Tengah Tahun 2020. Jenis penelitian ini adalah kuantitatif dengan design preeksperimental menggunakan pendekatan one grup pretets postest. Populasinya adalah seluruh ibu hamil Trimester III di BPM Sri Nowo Retno sebanyak 35 ibu hamil, sampel yang digunakan sebanyak 35 ibu hamil dengan teknik pengambilan sampel yaitu purposive sampling. Analisis data yang digunakan menggunakan uji paired t test. Hasil analisis didapatkan rata-rata kecemasan sebelum diberikan senam adalah 26.00, setelah diberikan senam adalah 22.40, nilai selisih rata-rata kecemasan sebelum dan sesudah diberikan senam yoga yaitu sebesar 3.600, kemudian didapatkan p-value sebesar 0,000 yang berarti ada pengaruh senam yoga terhadap tingkat kecemasan ibu hamil trimester III. Diharapkan hasil penelitian ini dapat digunakan sebagaisumber informasi untuk menambah pengetahuan ibu hamil, sehingga ibu hamil dapat menerapkan senam yoga sebagai salah satu metode untuk menurunkan rasa cemas.